Riddle Game in Elevating EFL Vocabulary Mastery - Devi, Govinda Kurnia; Rofiqoh, Rofiqoh; Anggreni, Afrillia; Suriaman, Aminah (Lectura : Jurnal Pendidikan, 2025)
Gaming in the language instructional process has been intensively implemented by academia all over the world and most of them claim that it is successful to bridge an English as Foreign Language (EFL) learner in mastering language skill and components. This study aims to expose how the implementation of riddle games elevating the vocabulary development of eighth grade students at junior high school (Sekolah Menengah Pertama/SMP Negeri 6 Palu. A quasi-experimental method was employed, consisting of experimental class that engaged in riddle game strategy meanwhile the control class received lecture method. 10 items of multiple choice, 5 items of jumbled words, and 10 items of matching vocabulary were used as the instrument to measure the student’s knowledge before and after getting intervention. The sample of 50 students in this research was randomly selected from the total population of 268 eighth grade students. Due to the non-normal distribution of the data, the Mann-Whitney U test was employed for statistical analysis. The finding demonstrates an improvement in the mean score of both groups; the experimental group improved from 41.56 to 55.16, while the control group increased from 44.88 to 49.24. However, the Mann-Whitney U ranks test showed a non-significant difference between the two classes (p>0.05). Thus, it can be concluded that the Riddle game is inefficient to expand students’ vocabulary mastery.